An Analysis On Writing Task Of English Textbook Entitled Bright For The Seventh Grade Students Of Junior High School - Prastian, Dita Ayuk, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
The research paper aims at describing the writing tasks that are appropriate with the criteria suggested by Raimes in English textbook entitled Bright and whether or not writing task in English textbook entitled Bright facilitate students in increasing writing ability. In analyzing the textbook, the writer uses descriptive research as the type of research. The data is writing tasks in English textbook entitled Bright. The method of data is document: (1) the writer reads an English textbook entitled Bright, (2) the writer analyzes the material contained in the textbook. The writer uses content analysis, the steps of procedure for analyzing data are as follows: (1) finding out the writing tasks provided in the textbook, (2) giving code in the material, (3) comparing writing task in the textbook with criteria writing task by Raimes, (4) giving the percentage to the total of writing task in textbook, (5) describing the writing task in the textbook is appropriate or not, (6) finding the percentage suitable writing task with criteria writing task by Raimes, (7) drawing conclusion based on the result of analysis, and giving some suggestion. The result of the research shows the percentages that writing task in English textbook entitled Bright is 64,28% because the writer finds nine criteria from fourteen criteria. The nine criteria that are suitable are addition, question answer, cloze test, conversion, scrambled paragraph, sentence combining, fill in the blank without translation, free composition in writing, and write the text based on the topic provided. The writer concludes that writing task in English textbook entitled Bright is good and appropriate with criteria suggested by Raimes. And also, the materials in English textbook entitled Bright facilitate the students in increasing writing ability.